The assessment of shadow economy in Lithuania - Narbuntaitė, Emilija; Ramanauskaitė, Agnė (Buhalterinės apskaitos teorija ir praktika, 2014)
In the scientific literature the shadow economy is defined as complex phenomena. The existence of it is determined by various causes and factors and the main purpose of this paper is to describe the meaning of shadow economy and estimate the size of it in Lithuania. The main tasks of this paper are to analyse the main conception of shadow economy, to present alternative methodologies for measuring the shadow economy, to analyse the level of shadow economy in Lithuania and disclose the main causes of it. The first part of the paper analyses the main conception of shadow economy. There are various points of view describing the definition of shadow economy and it depends on the main point of research. In this paper it is used the economical point of view. The second part of the paper presents the alternative methodologies for measuring shadow economy. There are various methods assigned to direct, indirect and factorial groups. Finally, in the third part of the paper it is presented the results of other authors’ researches of Lithuanian shadow economy. According to them, the rate of Lithuanian shadow economy fluctuates between 17-33.8% of gross domestic product. The most important Lithuanian shadow economy causes are too big tax burden, gaps in legislation, distrust and dissatisfaction of government.